First-principles calculations to investigate structural, elastic, electronic, and optical properties of XSrCl3 (X = Li, Na) - Jehan, Aiman; Husain, Mudasser; Sfina, Nourreddine; Khan, Saima Naz; Rahman, Nasir; Tirth, Vineet; Khan, Rajwali; Sohail, Mohammad; Rached, Ahmed Azzouz; Khan, Aurangzeb (Optik (Stuttgart), 2023)
The computational analysis of the compounds XSrCl3X=Li and Na is the subject of this research work. We utilized Density Functional Theory (DFT) to analyze the structural, optical, elastic, and electronic characteristics of XSrCl3(X=Li and Na) using the WIEN2K software. Birch Murnaghan curve optimization is performed to ascertain the structural details of both compounds. Using structural analysis, we learned that every compound displays a stable structural state at its optimum or ground state. The IRelast Package, which calculates elastic constants, is used to determine the elastic characteristics. Calculating these elastic characteristics reveals the compound's ductile or brittle nature, isotropy or anisotropy, and mechanical stability. Both materials are anisotropic and stable, as shown by an evaluation of elastic constants. Examining the Cauchy pressure, Poisson's ratio and Pugh ratio reveals that LiSrCl3 is a ductile compound while NaSrCl3 is brittle. We used generalized gradient approximation (GGA) to examine the electrical characteristics (Band Structure and Density of States). According to their computed band structures, these substances have wide indirect energy band gaps (R-Γ), or 3.57 eV for LiSrCl3 and 3.62 eV for NaSrCl3, which are indicative of semiconducting properties. To quantify the involvement of electronic states in the band structure, total and partial densities of states (TDOS and PDOS) are utilized. The optical characteristics of radiation up to 15 eV are estimated. Following an investigation of their optical properties, we measured these compounds' refractive indexes, absorption coefficients, and reflectivity. According to the anticipated electronic structure, the major optical spectrum peaks are listed.